SPEECH ACTS IN HITAM PUTIH PROGRAM ON TRANS 7 TELEVISION - Ananda Aulia Dalimunthe; Rahmad Husein (State University of Medan, 2014)
ABSTRACT This study deals with Speech Acts in HitamPutih Program on Trans 7 Television. The data were downloaded from internet on two episodes broadcasted in June 13th&14th, 2013. The utterances contained Speech Acts was identified and analyzed. This study applied descriptive qualitative method. The findings show that there were five types of Speech Acts in HitamPutih Talk Show namely: Directive 194 utterances (55.42%), Representative 80 utterances (22.85%), Expressive 21 utterances (6%), Commissive 8 utterances (2.28%) and Declaration 7 utterances (2%). Directive was the type used in the program HitamPutih. There were 194 items or (55.42%) which make it the most dominant type of Speech Acts used by the host, DeddyCorbuzier. This study shows that Directive was existed in HitamPutih Program. Keywords: Pragmatics, Sociolinguistics, Speech Acts.